Competencies revisited an educational approach to conceptualise planning as a boundary discipline - Gilliard, Lukas; Thierstein, Alain (AESOP, 2015)
The paper presents a systemic view on the purpose and impact of planning education. We introduce a system model, which bases upon the assumption that the objective of planning education is equipping students with competencies to resolve current and future challenges. Planning education has always focussed on instruments for this purpose. Among other reasons, established statutory instruments have become less effective in steering urban development due to a shift of power from public towards private stakeholders, e.g. in terms of funding. Thus, we propose a shift from formal qualifications suited for public planning control towards a problem-based and impact-orientated approach. The educational term ‘competence’ serves hereby as a measure of employability. The ‘wicked’ nature of planning problems distinguishes knowledge in planning. Knowledge is contextual and constantly transforming. It can however be deconstructed in a defined context. Then, we can assign an observable impact to a certain state of problem or intervention. These constructs of knowledge can help us to make informed decisions. The challenge is to apply and transform these contextual constructs to other settings. This requires proficiency in analysing, evaluating and creating constructs. Public planning control and its instruments consist of normative goals, which dictate the reason and extent of planning. In case of a problem-based approach, it is the role of a planner to recognise situations, in which his knowledge helps making an impact towards intended futures.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015